Análisis semántico de color, luz y transparencia en la arquitectura islámica de Irán - Sarbakhshian, Behnam (Innovaciencia, 2019)
The subject of color, including single colors or compounds like Haft Rang (seven colors), which conveys the psychological effectsand mystical interpretation of color, has a palpable presence in the realm of arts, especially in architecture. On the other hand,light as the most immaterial element of nature has always been present in Iranian architecture. In fact, it symbolizes transcendentalworld and spiritual realm. In traditional Iranian architecture, the conceptualization of light flourished under the influence of Islamicthought, and came to be known as the manifestation of sanctity and the spiritual world. This paper is an applied research, with ananalytical approach that seeks to conduct a semantic analysis of color, light and transparency in the Islamic architecture of Iran.The data was collected using the library research. Also, some illustrations of colors and light in Islamic architecture of Iran werephotographed and recorded in a field study. The analysis shows that Iranian architects have employed these factors in order to pleadto the observer’s sense of beauty by forging a close association between light and color in architecture. Diversity of colors, whichis rooted in divine wisdom, gives an appreciation of the beauty and dimensions to human beings. Moreover, the results suggest that theIranian architects have not been concerned with phenomenal clarity to create complexity, attractiveness, and spatial diversity, which areprimarily architectural aspects, but rather have focused on cultural objectives and excellence of human beings.